Synthesis, Characterization and Antioxidant Activity of Some New 3-(3-(Trifluoromethyl)phenyl)acrylic Acid Derived Hydrazide-Hydrazone Scaffolds - Pallapati, Ramya Krishna; Mutchu, Baby Ramana; Rao Vanga, Umamaheswara; Varala, Ravi; Bollikolla, Hari Babu (Asian Journal of Chemistry, 2020)
Some new analogues of trifluoromethylphenyl acrylic acid scaffold derived hydrazide-hydrazones (4a-l) were produced by using various structurally divergent aromatic aldehydes. All the hydrazones were obtained in moderate to good yields (64-78%) in methanol at a temperature of 45-65 °C. All the compounds were screened for antioxidant activity by DPPH method and the compounds 4c, 4d, 4e and 4h were found to be showed maximum antioxidant activity among the synthesized compounds.